THE ROLE OF SOCIAL MEDIA IN MODERN EDUCATION: ADVANTAGES AND CHALLENGES - Kamiljanova Risolat G‘afur qizi; Lola Xayrulloyeva Dilshod qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
There are many different types of social media that people use for different reasons; these social media include Instagram, YouTube, Telegram, and TikTok. These social media platforms can change how people learn and communicate with each other, and they provide an abundance of tools to allow for easy communication, interactions, and collaborations among users. Social media also helps students provide support to their creative learning process and to share the content they produce. There are many positive aspects associated with using social media as part of a student’s education; however, there are several negative aspects as well, including distractions, false information, and excessive usage of social media. This article will outline both the advantages and disadvantages of using social media in education, and it will discuss ways that social media can be used to enhance student engagement and to improve educational outcomes. In conclusion, social media can be a powerful educational resource; however, it should always be used in a responsible and thoughtful manner.